THE CORRECTIONS OF THE AL-MANAR'S AUTHOR, THE JURISPRUDENT, ON AL-ALUSI'S INTERPRETATION "AN ANALYTICAL STUDY." - Mohammed MahmoudAl- Sawadeh (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study dealt with The Corrections of the Al-Manar's Author, the jurisprudent of the spirit of meanings by Al-Alusi, in matters of jurisprudence. It aims to identify some of his corrections in this aspect, clarify its value, and reveal its truth; and the extent of its correctness.The importance of this topic lies in the encyclopedia of these two works, on the one hand: In the position of each of the two interpretations in the history of exegesis on the other hand, in addition to the owner of Al-Manar's great interest in the views of Al-Alusi in his interpretation, so he presented his statements, mentioned his jurisprudential and exegetical views and discussed them.The study was based on the two approaches: inductive and analytical, and came in an introduction, a preface, two chapters, and a conclusion, including results and recommendations, and concluded that his jurisprudential deductions have an essential explanatory value.